2020
DOI: 10.1371/journal.ppat.1008343
|View full text |Cite
|
Sign up to set email alerts
|

Novel role of SARM1 mediated axonal degeneration in the pathogenesis of rabies

Abstract: Neurotropic viral infections continue to pose a serious threat to human and animal wellbeing. Host responses combatting the invading virus in these infections often cause irreversible damage to the nervous system, resulting in poor prognosis. Rabies is the most lethal neurotropic virus, which specifically infects neurons and spreads through the host nervous system by retrograde axonal transport. The key pathogenic mechanisms associated with rabies infection and axonal transmission in neurons remains unclear. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 54 publications
(64 reference statements)
2
54
0
Order By: Relevance
“…For example, lyssavirus infection of neurons may result in mitochondrial dysfunction, producing oxidative stress and acute degenerative changes of neuronal processes 36 . In addition, one potential host-mediated response implicates a role for the SARM1 gene in axonal “self-destruction”, impeding viral spread but also with subsequent pathological impacts of neuronal and dendritic cell loss 37 .…”
Section: Pathogenesismentioning
confidence: 99%
“…For example, lyssavirus infection of neurons may result in mitochondrial dysfunction, producing oxidative stress and acute degenerative changes of neuronal processes 36 . In addition, one potential host-mediated response implicates a role for the SARM1 gene in axonal “self-destruction”, impeding viral spread but also with subsequent pathological impacts of neuronal and dendritic cell loss 37 .…”
Section: Pathogenesismentioning
confidence: 99%
“…SARM1 (sterile α and HEAT/armadillo motif–containing protein; Mink et al, 2001 ) was first discovered as a negative regulator of TRIF (TIR domain–containing adaptor inducing interferon-β) in TLR (Toll-like receptor) signaling ( Carty et al, 2006 ). SARM1 was later shown to promote neuronal death by oxygen and glucose deprivation ( Kim et al, 2007 ) and viral infections ( Hou et al, 2013 ; Mukherjee et al, 2013 ; Sundaramoorthy et al, 2020 ; Uccellini et al, 2020 ), while also having a protective role against bacterial and fungal infections in Caenorhabditis elegans ( Couillault et al, 2004 ; Liberati et al, 2004 ). Subsequently, studies have demonstrated that SARM1 is also a key part of a highly conserved axonal death pathway that is activated by nerve injury ( Gerdts et al, 2013 ; Osterloh et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mouse models and primary mouse neuronal cultures have been the preferred source to investigate rabies pathogenesis in-vivo and in-vitro, respectively. These model systems have identified several key pathogenic mechanisms, which have greatly improved our understanding of rabies [5,10,[35][36][37]. However, there are ethical and practical constraints which can limit the investigation of upstream neuronal pathogenic mechanisms in living animals and in primary neurons.…”
Section: Introductionmentioning
confidence: 99%